180k views
23 votes
What is f(3) if f(x) = –4x + 1?

2 Answers

11 votes

Answer:

f(3) = 13

Explanation:

4x3=12

f(3)=12+1

12+1=13

User Emax
by
4.8k points
6 votes

════════ ∘◦❁◦∘ ════════

Answer = -11

════════════════════

Known

f(x) = -4x + 1

════════════════════

Question

f(3) = ..?

════════════════════

Way to do

#since the x in (x) changed into (3) this means that the x change into (3)

f(3) = -4(3) + 1

f(3) = -12 + 1

f(3) = -11

════════════════════

User Jason Pawlak
by
4.9k points